STRATEGI PEMBELAJARAN MENGATASI KESULITAN ANAK SD DALAM MENGERJAKAN SOAL CERITA - HARAHAP, SUCI RAHMADANI; LUBIS, YUSMINA; SOFIYAH, KHOTNA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Math story problems can be a significant barrier to learning, requiring an understanding of math concepts and good reading skills. The aim of this research is to evaluate and detail effective learning strategies in overcoming elementary school children’s difficulties in solving math story problems. This research uses a literature review approach to detail various learning strategies that have been implemented and proven successful in improving elementary school children’s ability to handle math story problems. Some of the strategies evaluated include the use of contextual teaching materials, the application of problem-based learning methods, the integration of technology in mathematics learning, and the use of game-based activities to increase student motivation and involvement. The results of this literature review show that combining various learning strategies can have a positive impact on elementary school children’s ability to solve math story problems. Contextual teaching materials help students understand mathematical concepts better, while problem-based learning methods strengthen problem-solving skills. The use of technology in mathematics learning also provides variety and increases students’ interest in the subject. ABSTRAKSoal cerita matematika dapat menjadi hambatan signifikan dalam pembelajaran, memerlukan pemahaman konsep matematika dan keterampilan membaca yang baik. Tujuan dari penelitian ini adalah untuk mengevaluasi dan merinci strategi pembelajaran yang efektif dalam mengatasi kesulitan anak SD dalam menyelesaikan soal cerita matematika. Penelitian ini menggunakan pendekatan kajian literatur untuk merinci berbagai strategi pembelajaran yang telah diterapkan dan terbukti berhasil dalam meningkatkan kemampuan anak SD dalam menangani soal cerita matematika. Beberapa strategi yang dievaluasi meliputi penggunaan materi ajar yang kontekstual, penerapan metode pembelajaran berbasis masalah, integrasi teknologi dalam pembelajaran matematika, serta penggunaan aktivitas berbasis permainan untuk meningkatkan motivasi dan keterlibatan siswa. Hasil kajian literatur ini menunjukkan bahwa penggabungan berbagai strategi pembelajaran dapat memberikan dampak positif pada kemampuan anak SD dalam menyelesaikan soal cerita matematika. Materi ajar yang kontekstual membantu siswa memahami konsep matematika dengan lebih baik, sementara metode pembelajaran berbasis masalah memperkuat keterampilan pemecahan masalah. Penggunaan teknologi dalam pembelajaran matematika juga memberikan variasi dan meningkatkan minat siswa terhadap mata pelajaran tersebut.